Pinapple Farming Income in Belik District Pemalang Regency - Amalia, Ifa Firda; Setiadi, Agus; Handayani, Migie (JURNAL LITBANG PROVINSI JAWA TENGAH, 2023)
This study aims to determine the income of pineapple farmers and the factors that affect the income of pineapple farmers. The number of respondents used is 114 pineapple farmers in Bulakan Village and Belik Village, Belik District. The sampling method was carried out using the simple random sampling method. The results of the analysis show that the average income of pineapple farmers in Belik District, Pemalang Regency is Rp. 17,632,293/year. Capital, land area, price, farming experience, age, and education together affect the income of pineapple farmers. Capital, land area, and price have a positive and significant effect on the income of pineapple farmers. Farming experience, age and education have no effect on the income of pineapple farmers. Farmers should optimize their land usage by following recommended planting distances and efficiently managing the capital invested in farming activities, such as by using efficient production factors, to increase the income they receive.